Marine litter as a vector for non-native species: What we need to know. Issue 1 (15th December 2016) - Rech, Sabine; Borrell, Yaisel; García-Vazquez, Eva
Abstract: Plastic debris and other floating materials endanger severely marine ecosystems. When they carry attached biota they can be a cause of biological invasions whose extent and intensity is not known yet. This article focuses on knowledge gaps and research priorities needed for, first, understanding and then preventing dispersal of alien invasive species attached to marine litter. Highlights: Non-native species raft on floating anthropogenic litter over large distances (trans-oceanic) The role of anthropogenic flotsam in species introductions and local spread should be evaluated Source areas with a high occurrence of both floating litter and alien species should be identified Ports and aquaculture facilities are presumably important source areas of litter-rafting AIS Policies should reduce litter production, control source areas and protect potential sinks.